2015
DOI: 10.1016/j.egypro.2015.07.619
|View full text |Cite
|
Sign up to set email alerts
|

Lubricity Improvement of the Ultra-low Sulfur Diesel Fuel with the Biodiesel

Abstract: Ultra-low sulfur diesel fuel is essential requirement as per the emission regulation. With the adoption of hydrodesulfurization (HDS) process, the diesel fuel loses its inherent lubricity, however certain amount of lubricity of diesel fuel is needed to save several engine components from wear and failure. Though the loss of lubricity of the diesel fuel is observed with the removal of sulfur, it is mainly due to the loss of nitrogen and oxygen based polar trace compounds which are also removed in the HDS proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The presence of oxygen in the ester molecules induces a polarity phenomenon, which can explain the better lubricity results when esters are added to the gasoline. This result is similar to the ones found in other related studies (Farias et al, 2014;Hazrat et al, 2015), where a better lubricity is observed after biodiesel is combined with diesel fuel. These chemical polar species adsorb on the friction surface forming a protective film, preventing metal on metal contact and abrasion (Knothe et al, 2005;Nicolau et al, 2014).…”
Section: Film Formation and Coefficient Of Friction (Cof)supporting
confidence: 92%
See 1 more Smart Citation
“…The presence of oxygen in the ester molecules induces a polarity phenomenon, which can explain the better lubricity results when esters are added to the gasoline. This result is similar to the ones found in other related studies (Farias et al, 2014;Hazrat et al, 2015), where a better lubricity is observed after biodiesel is combined with diesel fuel. These chemical polar species adsorb on the friction surface forming a protective film, preventing metal on metal contact and abrasion (Knothe et al, 2005;Nicolau et al, 2014).…”
Section: Film Formation and Coefficient Of Friction (Cof)supporting
confidence: 92%
“…This happens because gasoline pumps are operated at high pressure conditions. In this context, there are few researches on gasoline lubrication and there is no standard test specifications set, while, in the case of diesel, there is a standard test in place to evaluate diesel lubrication (Fusco et al, 2005). Therefore, this study aims to assess the effect of oxygen additives such as ethyl octanoate and ethyl oleate on gasoline lubricity.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of ultralow sulphur fuel oil (ULSFO) differ completely compared with types of fuel MGO and MDO [11]. There are some other characteristics of fuel oil but in Table 4 only uses the main characteristics include the sulphur content, viscosity at 40°C, and flash point of fuel oil.…”
Section: Low Sulphur Fuel Oilmentioning
confidence: 99%
“…Therefore, the experimental conditions of operation to obtain a selective process that results in a high proportion of MG in the final FAME mixture, not only are much softer, but also there is no need to perform any additional purification operation, since glycerol is not produced, and the unreacted alcohol can be left as part of the mixture that constitutes the biofuel, so that the atomic efficiency of the process is practically 100% because all reagents are integrated in the final biofuel. Furthermore, in recent researches, it has been demonstrated that MG enhance the biodiesel lubricity as well [287][288][289][290][291][292][293][294][295].…”
Section: Biodiesel-like Biofuels That Integrate Glycerol As Monoglycementioning
confidence: 99%